Validity of E-LKPD to Train Students' Critical Thinking Abilities - Aini, Nur; Putri, Rossanita Truelovin Hadi (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Changes in the development of science and technology (IPTEK) mean that teachers are obliged to continue to develop learning so that students are able to develop in the 21st century era. In the 21st century, learning requires supporting learning tools in the form of good learning tools that are acceptable to students. One of them is using electronic student worksheets. The aim of this research is to determine the validity of electronic learning media for Student Worksheets based on a scientific approach to cell material to train students' critical thinking based on validation results from media and material experts. This research uses a 4D development model, data collection instruments in the form of validation sheets. Validity testing is carried out by media and material expert validators. The results of the research show a value of 86.00% carried out by media experts, which means it is feasible and the value made by material experts is 84.00%, which means it is suitable for use.